The Mental Health Effects and Experiences of Breastfeeding Decision-Making Among Postpartum Women Living with HIV. - Harris, Leah R.; Lee, Do H.; Mareuil, Joanna W.; Rakhmanina, Natella Y.; Koay, Wei Li A. (AIDS & Behavior, 2024)
Prior to January 2023, women living with HIV (WLWH) in the United States (US) were discouraged from breastfeeding due to the potential risk of mother-to-child HIV transmission through breastfeeding. Lack of breastfeeding decision-making and experience among WLWH may negatively affect maternal mental health. We implemented a quality improvement initiative to screen WLWH for postpartum depression (PPD), evaluate their attitudes toward breastfeeding, and assess their experience with breastfeeding decision-making. We collected quantitative data from WLWH using a voluntary, self-administered 6-item breastfeeding decision-making and experience survey (administered 1 month postpartum) and a 10-item Edinburgh Postnatal Depression Scale (EPDS, negative = 0–9; administered 1 and 4 months postpartum) tool. We conducted descriptive statistics and cross tabulation analysis. We analyzed 106 WLWH (93.4% non-Hispanic Black/African American; mean age 33.1 years; 82.1% HIV RNA < 200 copies/mL). One in five (19.1%) WLWH had a positive baseline EPDS screen, with the mean EPDS scores decreasing from 5.3 ± 5.4 (baseline) to 4.6 ± 4.8 (follow-up). Among 55 WLWH who provided baseline and follow-up EPDS scores, only 3/13 with a positive baseline EPDS screen had resolved depressive symptoms at follow-up. Over one-third (37.7%) of WLWH indicated feeling "sadness" when asked whether lack of breastfeeding negatively affected their feelings or emotions. Over half of WLWH (51.9%) were aware of the US breastfeeding recommendations, but the majority (60.4%) had never discussed breastfeeding options with a medical provider. Improved provider–patient discussions on infant feeding options among WLWH is needed to increase awareness of breastfeeding choices and promote informed, autonomous breastfeeding decision-making among WLWH.